2018
DOI: 10.1136/bmjopen-2017-020512
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Asian patients with breast cancer: a systematic review

Abstract: ObjectiveTo summarise the evidence on determinants of health-related quality of life (HRQL) in Asian patients with breast cancer.DesignSystematic review conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations and registered with PROSPERO (CRD42015032468).MethodsAccording to the PRISMA guidelines, databases of MEDLINE (PubMed), Embase and PsycINFO were systematically searched using the following terms and synonyms: breast cancer, quality of life and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
88
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 104 publications
7
88
1
6
Order By: Relevance
“…Most QoL studies of breast cancer patients have shown that younger age was a risk factor for lower QoL as well as for significant stress after treatment 15,[16][17][18][19] . On the other hand, it has been observed that there was an improvement in the perceived QoL in all domains regardless of therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…Most QoL studies of breast cancer patients have shown that younger age was a risk factor for lower QoL as well as for significant stress after treatment 15,[16][17][18][19] . On the other hand, it has been observed that there was an improvement in the perceived QoL in all domains regardless of therapeutic modality.…”
Section: Discussionmentioning
confidence: 99%
“…16 Given that the majority of the research on PROs has been conducted in developed or HICs, it is important to understand the differences or similarities in how women in low and middle income countries (LMICs) interpret their cancer care priorities. 17,18 In LMICs, the differences in socioeconomic status, 19 health literacy, 20 the condition of the healthcare system, and various mitigating factors could deeply influence the perceptions and outcomes for breast cancer survivors. Therefore, we hypothesize that breast cancer survivors' priorities will differ between LMICs and HICs, as well as within populations.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was found that overall QOL is reduced and is consistently lower in patients receiving chemotherapy (Wöckel et al, ). According to the recently published systematic review, chemotherapy is a significant factor that affects overall QOL in breast cancer patients, but the effects of age, stage and other treatment including surgical method are unclear (Ho et al, ). This is consistent with our findings that only chemotherapy is a factor affecting overall QOL among the factors associated with the cancer‐related treatments and cancer itself.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the importance of rehabilitation for improving HRQOL and physical limitations of breast cancer survivors has been emerged (Foley, Hasson, & Kendall, ; Leclerc et al, ; Simonavice et al, ). Previous cancer rehabilitation has targeted patients who have been completed treatment for breast cancer, but since the HRQOL of breast cancer patients is reduced immediately after the surgery, there is a growing interest in rehabilitation for patients during breast cancer treatment (Fu et al, ; Ho, Gernaat, Hartman, & Verkooijen, ). One of the recent trends in the rehabilitation approach of breast cancer patients is early, multidisciplinary palliative rehabilitation, reflecting claims that comprehensive rehabilitation should be provided early to patients during cancer treatment (Leclerc et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation